KELAYAKAN CERITA BERGAMBAR PADA SUB MATERI KEANEKARAGAMAN JENIS DI KELAS X SMA SINTANG - Aswadi, Aswadi; Syamswisna, Syamswisna; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to describe the feasibility of picture story as learning media on species diversity submaterial in 10th grader on senior high school using descriptive quantitative method. It picture story feasibility was tested by five validators, one lecture of Biology Educational Study Program and one lecture of Bahasa Indonesia Educational Study Program, FKIP Untan and three high school Biology teacher. This research used validation sheet as research instrument with likert scale. School partner was selected by using simple random sampling technique.Â Those selected school were Sepauk 1st State Senior High School, Tebelian 1st State Senior High School, and Borneo Sepauk Senior High School. There were four aspects which tested by the validators, those where format aspect, content aspect, language aspect, and effective aspect . As result, picture stories was stated as valid and feasible to be used as learning media, with validation value 3,7. Â Keywords: Media, Picture Story, Validation.